2015
DOI: 10.1186/s13058-015-0580-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular drivers of lobular carcinoma in situ

Abstract: Lobular carcinoma in situ (LCIS) is considered to be a risk factor for the development of invasive breast carcinoma, but it may also be a non-obligate precursor to invasive lobular carcinoma (ILC). Many LCIS lesions do not progress to ILC, and the molecular changes that are necessary for progression from LCIS to ILC are poorly understood. Disruption in the E-cadherin complex is the hallmark of lobular lesions, but other signaling molecules, such as PIK3CA and c-src, are consistently altered in LCIS. This revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 101 publications
1
35
0
1
Order By: Relevance
“…Further, there was no significant difference in the pattern of CDH1 mutations between LCIS and ILC samples. Previous studies with smaller sample sizes and different methodology have reported a higher frequency of CDH1 mutations in ILC (Logan et al., 2015); however, our findings are consistent with that of the most recent publication from The Cancer Genome Atlas Project, where CDH1 mutations were identified in 63% (80/127) of classic invasive lobular carcinomas (Ciriello et al., 2014, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Further, there was no significant difference in the pattern of CDH1 mutations between LCIS and ILC samples. Previous studies with smaller sample sizes and different methodology have reported a higher frequency of CDH1 mutations in ILC (Logan et al., 2015); however, our findings are consistent with that of the most recent publication from The Cancer Genome Atlas Project, where CDH1 mutations were identified in 63% (80/127) of classic invasive lobular carcinomas (Ciriello et al., 2014, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…All cell lines grew without hormone supplements with engraftment rates between 30% and 100% with the exception of MDAMB231 cells, which grew only in 1 out of 26 grafts ( Figure 1B). The findings included ER + cell lines, such as the most widely studied MCF7 (Lee et al, 2015), HCC1428, ZR751, and MDAMB134VI, which is derived from a lobular carcinoma and does not seem to have been established in vivo previously (Logan et al, 2015), as well as the androgen receptor (AR) + MDAMB453 (Figures 1B, S1A, and S1B), which usually requires exogenous 5a-dihydrotestosterone (Ni et al, 2011). In vivo monitoring of engrafted mice by luminescence showed that the ER + cell lines grow exponentially ( Figure 1C).…”
Section: Intraductal Growth Of Breast Cancer Cell Linesmentioning
confidence: 99%
“…Current biomarker data in LCIS are very limited [16]. There is some evidence to suggest the risk of subsequent invasive disease is associated with high Ki67 expression [17] and that increased expression of hsa-miR-375 contributes to lobular neoplastic progression [18].…”
Section: Introductionmentioning
confidence: 99%